Analisis Sistem Penyelenggaraan Rekam Medis di Instalasi Rekam Medis RS “X” Tangerang Periode April-Mei 2015 - Nuraini, Novita (UI Scholars Hub, 2015)
This study aims to analyze the medical records implementation system (input, process, output, feedback and control) in the